Guerreiro Ramos: the course of a thought - Soares, L. A. Alves (1995)
The thinking of Guerreiro Ramos had its beginnings while he was stillliving in Bahia, even before he started his course on Social Studies in Rio de Janeiro, at then Universidade do Brasil. Presenting itself in distinct phases, his work is not, however, fashioned as a .series of tigbt compartments.